Volvulus of gall bladder: case report - Kumar, Rajneesh; Hastir, Ankur; Walia, Ramandeep Singh; Goyal, Subhash (International Surgery Journal, 2017)
Gall bladder volvulus or twisting is a rare condition and occurs due to rotation of gall bladder. Preoperative diagnosis is exception and usually misdiagnosed as cholecystitis before surgery. It is potentially fatal condition unless diagnosed and treated early leading to gangrene and biliary peritonitis. It has been reported in only about 500 cases in the literature ranging in age given 2-100 years old. We report a rare case of middle aged female 56 years old with volvulus of gall bladder having concomitant cholelithiasis treated with laparoscopic cholecystectomy.